Changes in procyanidins and tannin concentration as affected by cocoa liquor roasting - Misnawi Jati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2009)
Changes in cocoa procyanidins and tannin concentration as affected by cocoa liquor roasting were studied by heating up cocoa liquor of fermented beans containing 58 g kg-1 of polyphenols and the same liquor which was enriched with crude polyphenols, extracted from freeze-dried unfermented cocoa beans to a final concentration of 170 g kg-1. The liquors were roasted at 120 OC for 15, 25, 35 and 45 min with three replications. Result of the study showed that cocoa bean polyphenol was resistant against high temperature during heating of cocoa liquor 120 OC for up to 45 min. The resistance was stronger with the unfermented cocoa bean polyphenol than with fermented cocoa. High temperature promoted a small quantity of monomers up to pentamers of the fermented cocoa bean polyphenol to polymerize into higher oligomers, but did not with unfermented cocoa bean polyphenol. These results imply that the problem of lack in cocoa flavor in terms high astringency and bitterness due to high polyphenol content cannot be overcome by the application of high temperature during chocolate processing, meanwhile cocoa bean polyphenol could still give beneficial as an antioxidant even after high temperature application.Key words: Cocoa bean, polyphenol, procyanidin, tannin, roasting, antioxidant, flavor, astringency.